2020
DOI: 10.3390/nu12082349
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intermittent Fasting Combined with Resistance Training on Lean Body Mass: A Systematic Review of Human Studies

Abstract: Diets utilising intermittent fasting (IF) as a strategic method to manipulate body composition have recently grown in popularity, however, dietary practices involving fasting have also been followed for centuries for religious reasons (i.e., Ramadan). Regardless of the reasons for engaging in IF, the impacts on lean body mass (LBM) may be detrimental. Previous research has demonstrated that resistance training promotes LBM accrual, however, whether this still occurs during IF is unclear. Therefore, the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
2
29
0
1
Order By: Relevance
“…Many of the studies mentioned above prescribe variations of IF as the independent variable but do not explicitly control dietary intake ( 19 , 69 , 70 , 72 78 , 81 , 89 , 90 ) and/or physical activity ( 19 , 69 72 , 75 78 , 80 , 89 , 90 ), the latter of which is important to consider given that spontaneous physical activity may be modified by restricted eating ( 91 ) and can also influence the sensitivity of skeletal muscle to dietary AA ( 92 ). When IF is coupled with the potent anabolic stimulus of resistance exercise, a systematic review ( 93 ) observed no significant differences in FFM outcomes when compared to those resistance training with a normal diet. However, given the normal diet group also did not experience gains in FFM, as would be expected, the length (i.e., 4–8 weeks) of the included studies may also not have been adequate to reliably measure changes in FFM.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies mentioned above prescribe variations of IF as the independent variable but do not explicitly control dietary intake ( 19 , 69 , 70 , 72 78 , 81 , 89 , 90 ) and/or physical activity ( 19 , 69 72 , 75 78 , 80 , 89 , 90 ), the latter of which is important to consider given that spontaneous physical activity may be modified by restricted eating ( 91 ) and can also influence the sensitivity of skeletal muscle to dietary AA ( 92 ). When IF is coupled with the potent anabolic stimulus of resistance exercise, a systematic review ( 93 ) observed no significant differences in FFM outcomes when compared to those resistance training with a normal diet. However, given the normal diet group also did not experience gains in FFM, as would be expected, the length (i.e., 4–8 weeks) of the included studies may also not have been adequate to reliably measure changes in FFM.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated a significant increase in lean mass (1.0-1.4 kg) over the 8-week period for all groups compared to baseline with no between-group differences. All groups significantly increased their total energy intake during the intervention, which may have contributed to the significant increase in lean mass observed in contrast to other combined fasting and exercise studies that had an energy balance or deficit [40,68,69]. Moreover, this study was conducted in young, trained female participants and its applicability to the male, un-trained, and cancer populations is limited.…”
Section: Combined Fasting and Exercisementioning
confidence: 90%
“…However, when food is not supplied, the body relies on processes of biosynthesis as well as stored glycogen, fats, and proteins as metabolic fuel substrates [38]. Therefore, the metabolic substrates, and their catabolic or anabolic pathways, differ in a fed state from a fasted state and is likely one of the key mechanisms responsible for many of the changes observed when undertaking fasting compared to a fed intervention [39,40]. In a fed state, the body predominantly utilizes glucose from the recently consumed meal as the primary source of fuel via glycolysis, oxidative phosphorylation, and carbohydrate oxidation [38,41,42].…”
Section: What Metabolic Changes Occur During Fasting and Exercise?mentioning
confidence: 99%
See 2 more Smart Citations